The Implementation Of Strategic Planning In Improving Education Quality: Swot Analysis As A Key Instrument - Syahril Yusuf; Ilham Wahyudi; Mainur Adriyana; Muhammad Syaifuddin (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine and find out the implementation of strategic planning in improving the quality of education at UPT SDN 032 Kualu and to examine and find out the supporting and inhibiting factors for the implementation of strategic planning in improving the quality of education at UPT SDN 032 Kualu. This research uses a qualitative approach, as an effort to provide answers to the problems that have been described, because it uses a descriptive analysis approach using data collection techniques through observation, interviews and documentation. With data analysis techniques, namely: data reduction, data presentation, conclusion drawn, and data tringulation. The results of the study can be concluded that: (1) The implementation of strategic planning in improving the quality of education at UPT SDN 032 Kualu has been implemented, the use of strategic plans in improving quality is very helpful, with a plan prepared with strategic decisions is certainly able to facilitate the implementation of school quality improvement,   with the use of environmental SWOT analysis which is part of the strategic plan can help by looking at strengths,  friendliness, opportunities and threats owned by schools and that schools will face in the future. (2) Supporting factors, the role of the school principal, good cooperation, quality human resources, regular evaluation, having guidelines in carrying out activities to improve the quality of education. Inhibiting factors, inadequate programs, facilities and infrastructure, gaps between school curriculum and government policies, and lack of creativity of teachers make it difficult to understand technological developments.